2003
DOI: 10.1081/ese-120019864
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Reproductive Effects of Low Cadmium Concentration onArtemiaparthenogenetica

Abstract: Hatching, reproductive, and lifespan characteristics of an Artemia parthenogenetica population from La Mata (Alicante, Spain) exposed to cadmium were studied. No effects on percentage of cyst hatched nor time of hatching were observed on cysts exposed from 0.01 to 5 mg Cd/L. Cohorts of Artemia were chronically exposed to cadmium in life-table experiments to test whether ecologically relevant impacts may occur after several generations of exposure to a very low concentration of cadmium. Chronic toxicity tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Our findings are in agreement with the results of Raikow et al (2006Raikow et al ( , 2007, who observed that the biocide SeaKlean had significant negative effects on hatching of D. mendotae dormant eggs, but with a ten times lower sensitivity compared to neonate mortality (Song et al 2011). Studies using dormant eggs of other zooplankton species (mainly rotifers and Artemia) gave variable results; ranging from no significant adverse effects on hatching rates (Sarabia et al 2003(Sarabia et al , 2008Varó et al 2006;Marcial and Hagiwara 2007), to effects on unhatched embryos at concentrations below effect levels for hatched individuals Rafiee et al 1986). This indicates that effects of chemicals on dormant stages differ among and within species as well as among toxicants, depending on their mode of action.…”
Section: Impact Of Pesticides On Hatching Growth and Reproductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are in agreement with the results of Raikow et al (2006Raikow et al ( , 2007, who observed that the biocide SeaKlean had significant negative effects on hatching of D. mendotae dormant eggs, but with a ten times lower sensitivity compared to neonate mortality (Song et al 2011). Studies using dormant eggs of other zooplankton species (mainly rotifers and Artemia) gave variable results; ranging from no significant adverse effects on hatching rates (Sarabia et al 2003(Sarabia et al , 2008Varó et al 2006;Marcial and Hagiwara 2007), to effects on unhatched embryos at concentrations below effect levels for hatched individuals Rafiee et al 1986). This indicates that effects of chemicals on dormant stages differ among and within species as well as among toxicants, depending on their mode of action.…”
Section: Impact Of Pesticides On Hatching Growth and Reproductionsupporting
confidence: 82%
“…The results of different studies using Artemia cysts, however, appear to be inconclusive. Varó et al (2006) and Sarabia et al (2003Sarabia et al ( , 2008 reported no adverse effects of metal and pesticide exposure on hatching of Artemia cysts. Bagshaw et al (1986) and Rafiee et al (1986), on the contrary, reported that hatching of dormant eggs was more sensitive to heavy metal exposure than hatched individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Carballo et al (2002) found high concordance between mortality of nauplii and hatchability of cysts (measured as the number of nauplii hatched from a known weight of cysts in treatment and control) exposed to different organic extracts, suggesting a simultaneous application of both the assays. Also Sarabia et al (2003) had consistent results comparing chronic toxicity tests on nauplii and percentage and timing of cyst hatching under cadmium exposure: no effects were found neither with nauplii nor with cysts. Caldwell et al (2003) compared the hatching success (as enumeration of random chosen subsamples of hatched nauplii) and larval mortality (48 and 72 h) of A. salina exposed to diatom extracts or aldehydes, finding the hatching assay as the least sensitive test.…”
supporting
confidence: 49%
“…Most of the efforts were focused on acute toxicity studies (Okamura et al 2000;Hadjispyrou et al 2001;George-Ares et al 2003;Mayorga et al 2010;Leis et al 2014). At a lesser extent, investigations have been focused on long term, subchronic and chronic exposures (Brix et al 2003;Sarabia et al 2003;Savorelli et al 2007;Bustos-Obregon and Vargas 2010). Acute tests with Artemia are known to show low sensitivity; while, prolonged exposure assays, although more sensitive, require quite complex procedures, discouraging their use.…”
mentioning
confidence: 99%
“…Artemia spp. can accumulate Cd through solution and food, and exposure interferes with emergence and hatching and may impact reproduction (Jennings & Rainbow 1979b, Sarabia et al 2002a). The cyst shell of Artemia spp.…”
Section: Introductionmentioning
confidence: 99%